Designing, implementing, and evaluating a gamification approach in childbirth training for midwifery students using computer and mobile application - Fereshteh Behmanesh; Zeinab Gholamnia-Shirvani; Saeideh Ghaffarifar; Hossein-Ali Nikbakht; Sana Nazmi (BMC Medical Education)
Abstract Background Clinical education is a cornerstone in equipping medical science students with essential skills. Improving the quality of childbirth protocol training for midwifery students through innovative and engaging approaches can significantly enhance learning outcomes and student interest. This study aimed to design, implement, and evaluate a gamified approach to childbirth protocol education for midwifery students via computer and mobile applications. Method This scholarship study was carried out with 34 midwifery students at Babol University of Medical Sciences during the second semester of the 2024 academic year. Students were selected via census sampling and randomly assigned to two groups in a crossover design. Six topics related to the childbirth protocol were taught through gamification. One group (intervention) learned half of the topics via this method, whereas the other group (control) used traditional teaching methods. The remaining topics were then taught in reverse order to both groups. Preintervention data collection included demographic information and Sibria Sherring’s emotional intelligence questionnaire. Knowledge and performance were assessed at the maternal bedside before and four weeks after the intervention. A satisfaction survey on the training method was conducted four months postintervention. The data were analyzed via SPSS 28, with a significance level of p < 0.05. Findings Among the 34 midwifery students, with a mean age of 21.82 ± 1.48 years, the gamified group presented significantly higher mean knowledge scores four weeks postintervention than did the traditional group did (mean difference: 1.91, 95% CI: 0.97–2.84, p < 0.001). Similarly, the mean performance scores in the gamified group were significantly greater (mean difference: 2.80, 95% CI: -2.06 - -3.54, p < 0.001). Additionally, satisfaction with the gamified method was significantly greater than that with traditional methods (mean satisfaction difference: 8.97, 95% CI: 12.36–5.58, p < 0.001). Conclusions The findings highlight that gamification not only improves midwifery students’ knowledge of delivery protocols but also enhances their practical skills, which are critical for improving maternal care and infant health. The higher satisfaction levels observed suggest the effectiveness of gamification in fostering student engagement. Therefore, the integration of interactive learning and gamification into midwifery education programs is recommended.